A hydrogenated hydroxy-terminated butadiene–acrylonitrile copolymer-based polyurethane elastomer with improved mechanical properties and aging resistance. Issue 24 (18th February 2016) - Zou, Rui; Tan, Jing; Liu, Kun; Liang, Lu; Cheng, Xingwang; Zhang, Xu; Zhang, Liqun; Yue, Dongmei
Abstract : A hydrogenated hydroxy-terminated butadiene–acrylonitrile copolymer (HHTBN)-based polyurethane elastomer (PUE) was prepared by using HHTBN as the soft segments in a casting method. Abstract : A hydrogenated hydroxy-terminated butadiene–acrylonitrile copolymer (HHTBN)-based polyurethane elastomer (PUE) was prepared by using HHTBN as the soft segments in a casting method. The HHTBN-based PUE exhibited improved mechanical properties and aging resistance.